Grandparenting and adolescent adjustment in two-parent biological, lone-parent, and step-families - Shalhevet, Attar Schwartz; Tan, Jo Pei; Ann, Buchanan; Eirini, Flouri; Julia, Griggs (US: American Psychological Association, 2009)
There is limited research on the links between grandparenting and adolescents' well-being, especially from the perspective of the adolescents. The study examined whether grandparent involvement varied in two-parent biological, lone-parent, and step-families and whether this had a different contribution to the emotional and behavioral adjustment of adolescents across different family structures. The study is based on a sample of 1,515 secondary school students (ages 11-16 years) from England and Wales who completed a structured questionnaire. Findings of hierarchical regression analyses showed that among the whole sample, greater grandparent involvement was associated with fewer emotional problems (p < .01) and with more prosocial behavior (p < .001). In addition, while there were no differences in the level of grandparent involvement across the different family structures, grandparent involvement was more strongly associated with reduced adjustment difficulties among adolescents from lone-parent and step-families than those from two-parent biological families. A possible implication is that the positive role of grandparent involvement in lone-parent and step- families should be more emphasized in family psychology.